Skiing Trauma and Safety: Eighth International Symposium 1991
DOI: 10.1520/stp17651s
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Risk Factors for Ski Injury: Problem Analysis as a Basis for Effective Health Education

Abstract: A problem analysis dealing with the importance of behavioral risk factors for ski injuries is based on the results of a case-control study conducted among Dutch skiers. In this study, cases (N = 572) were a sample of those who filed insurance claims for medical costs incurred as the result of a ski injury that prevented them from skiing for more than one day. Controls (N = 576) were a sample of uninjured skiers who filed insurance claims for nonmedical reasons. Not taking ski lessons appeared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…2, 5-7, 15, 20, 26, 27 It has been suggested that the development of a tailormade prevention program aimed at younger children (12 years and younger) would significantly contribute to the reduction of skiing injuries among this age group. 4,23 Systematic planning of a skiing injury prevention program includes analyzing the magnitude of the problem and the behavioral risk factors, studying behavioral determinants, designing an optimal intervention, and implementing the intervention. 23 For most sports, there seems to be a strong need for further research on the origins and determinants of behavior before effective prevention can be implemented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2, 5-7, 15, 20, 26, 27 It has been suggested that the development of a tailormade prevention program aimed at younger children (12 years and younger) would significantly contribute to the reduction of skiing injuries among this age group. 4,23 Systematic planning of a skiing injury prevention program includes analyzing the magnitude of the problem and the behavioral risk factors, studying behavioral determinants, designing an optimal intervention, and implementing the intervention. 23 For most sports, there seems to be a strong need for further research on the origins and determinants of behavior before effective prevention can be implemented.…”
mentioning
confidence: 99%
“…At least two studies suggest that the risk of injury for children is increased by not having received any formal ski lessons, 10,32 whereas other studies have reported no difference. 4,31 Shealy et al 33 concluded that the rapid skill acquisition through lessons when not coupled with much skiing experience was not sufficient for reducing the injury rate. Garrick and Requa 14 argued that skiers appear to be in a paradoxical situation whereby they can ski more safely if they are better skiers, but rapidly gaining that expertise through lessons may mean an increase, although probably temporary, in injuries.…”
mentioning
confidence: 99%
“…In the majority of studies done in North America and Europe, skiing lessons did not decrease the risk of personal injury 3,4,18,20,30,34,58. From the earliest studies18,30,58 to the present,3,4,20,34 researchers have shown that lessons are not an effective method for reducing injury risk.…”
Section: Mythmentioning
confidence: 98%
“…In the majority of studies done in North America and Europe, skiing lessons did not decrease the risk of personal injury. 3 , 4 , 18 , 20 , 30 , 34 , 58 From the earliest studies 18 , 30 , 58 to the present, 3 , 4 , 20 , 34 researchers have shown that lessons are not an effective method for reducing injury risk. In contrast, Ekeland and colleagues have reported that ski instruction in Norway was associated with fewer injuries, when comparing an injured population with an uninjured control group.…”
Section: Mythmentioning
confidence: 99%